Comparison of physiological and perceptual load between uke and tori after intermittent osaekomi-waza exercise in judo - Ceylan, B.; Balci, S. S. (International Journal of Performance Analysis in Sport, 2022)
This study investigated differences in physiological and perceptual responses between uke and tori during intermittent osaekomi-waza exercise. Twenty-one male judo athletes voluntarily participated in this study. Following anthropometric measurements and 1 min uchi-komi test, athletes executed 20 s × 6 sets (1:½ work rest ratio) intermittent osaekomi-waza exercise with kesa-gatame as both uke and tori. Athletes` heart rate and lactate concentration were monitored at rest, 1 min, and 6 min following the exercise while the athletes classified the rate of perceived exertion just after the exercise. During the experiment, the changes in heart rate were different between positions with higher values in uke position compared to tori position after the intermittent exercise (F2,40 = 4.28, p = 0.03). Moreover, athletes in the uke position stated a higher rating of perceived exertion than athletes in the tori position (p = 0.01). However, blood lactate responses were found to be similar between positions (p > 0.05). Intermittent osaekomi-waza exercises resulted in similar metabolic load for uke and tori positions, while higher cardiovascular load was observed in the uke position compared to the tori position. Thus, it can be concluded that the athletes in uke position are exposed to more cardiovascular load compared to those in tori position and present higher perceptual responses.